Religious and Spiritual Growth Goals: A Forgotten Outcome. (January 2022) - Patrick, Julie Hicks; Carney, Amy Knepple; Ebert, Alexandria R.
Religious and spiritual (R/S) growth goals have been forgotten among self-improvement goals. We used social cognitive theory, useful in other domains of self-improvement, to study R/S goals. Data from 350 adults ( M age = 40.5, SD = 14.6) were used to examine the relations among age, gender, social interactions, and commitment to R/S goals and physical activity goals. Results of the path analysis, X 2 (DF = 2, N = 350) = 9.91, p < .01, showed similar contributions of positive social interactions to persistence on both goals. Differences between the two outcomes included a direct effect of age ( β = .18), dissatisfaction with negative social interactions ( β = .12), and satisfaction with positive social exchanges ( β = .15) on persistence on R/S goals. Only positive social exchanges ( β = .31) related to physical activity goals. The results are discussed in terms of the feasibility of applying goal-striving frameworks to the examination of R/S growth goals.